Moral Issues and Motive of Loneliness In "Kite Runner" and “A Thousand Splendid Suns” By Khaled Hosseini - Xayatovna, Niyazova; Abdurasulovna , Azizova (Pubmedia Social Sciences and Humanities, 2025)
This study examines the moral dilemmas and themes of loneliness in Khaled Hosseini’s The Kite Runner and A Thousand Splendid Suns within the cultural and historical backdrop of Afghanistan. The novels highlight the struggles of their protagonists as they navigate betrayal, redemption, and social injustice. The research employs a literary analysis methodology, focusing on character development, symbolism, and moral decision-making. It explores how Amir’s journey in The Kite Runner reflects personal redemption, while A Thousand Splendid Suns emphasizes resilience and female solidarity in the face of oppression. Findings suggest that loneliness emerges from both internal guilt and external societal constraints, yet is ultimately transformed through sacrifice and human connection. Hosseini’s works underscore the triumph of moral integrity over suffering, making them both powerful literary narratives and reflections on universal human values. The article is devoted to analyzing morality and the motive of loneliness in Khaled Hosseini's “Kite Runner” and “A Thousand Splendid Suns”. In the setting of Afghanistan's culture, these books examine difficult human experiences like moral decisions, treachery, redemption, and loneliness.